Implikasi Frekuensi Pemanfaatan Media Sosial Terhadap Interaksi Sosial Dan Motivasi Belajar Pendidikan Agama Buddha Siswa Smp Swasta di Kota Makassar - Zeindi Zetiawan Yanwar (Universitas Hamzanwadi, 2026)
The term “intensity” refers to the strength of behavior related to the level of energy used to express emotions. In general, intensity is defined as the manifestation of an individual’s effort to achieve the desired goals. This study aims to analyze the impact of the intensity of social media use on social interaction and learning interest in Buddhist Religious Education among students of private junior high schools in Makassar City. The research employs a quantitative approach with a descriptive and correlational design, using data obtained from questionnaires. The sample consists of 100 Buddhist junior high school students, selected through purposive sampling. Data analysis was carried out using simple linear regression and correlation tests. The results indicate a positive and significant influence between variable X and Y1, showing that the intensity of social media use significantly affects students’ social interaction, with a regression coefficient of 0.334, a t-value of 4.576, and a significance level of <0.001. Meanwhile, regarding the relationship between variable X and Y2, the findings show a positive and significant influence of social media use intensity on students’ interest in learning Buddhist Religious Education, with a regression coefficient of 0.393, a t-value of 5.357, and a significance level of <0.001. These findings demonstrate that social media plays a role in facilitating communication and social relationships, both inside and outside the school environment. The study concludes that learning interest has a very strong and significant effect on students’ social interaction. Thus, students who have high interest and motivation in learning tend to be more active in interacting with their social environment.